Resolution of Right Hemidiaphragm Paralysis following Cervical Foraminotomies - Neal Singleton; Matthew Bowman; David Bartle (Case Reports in Orthopedics)
Introduction. Hemidiaphragm paralysis secondary to phrenic nerve palsy is a well-recognised medical condition. There are few case reports in the literature documenting resolution of hemidiaphragm paralysis following cervical spine surgery. This case report documents our experience with one such case. Case Presentation. A 64-year-old man was referred to the orthopaedic service with right hemidiaphragm paralysis. He had a previous history of asbestos exposure and polio and was initially seen and investigated by the respiratory physicians. He also reported intermittent neck pain and an MRI scan showed right-sided cervical foraminal stenosis. He underwent posterior right C3/4 and C4/5 foraminotomies, and by three months postoperatively, his hemidiaphragm paralysis had resolved and his shortness of breath had also improved. Conclusion. This report documents a unique case of resolution of hemidiaphragm paralysis following posterior unilateral cervical foraminotomies.